Geotechnical Map for the City of Nablus - Palestine - Isam Jardaneh (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Geotechnical maps are widespread nowadays due to the existence of Geographical Information Systems (GIS) and Global Position Systems (GPS). These maps provide a powerful database and strong visual presentation of data. The use of such maps will save effort, time, and provide quick source of information for engineering projects, especially in civil engineering field, such as the construction buildings, dams, roads, tunnels, etc.. There are several types of geotechnical maps; however, the map that is considered here is for allowable bearing capacity and proposed type of foundation for the City of Nablus - Palestine. The importance of such a map is the fast and simple access to the information regarding foundation, allowable bearing capacity, problems due to site soil such as sliding, potential swelling and shrinkage, and cavities. In addition, this map will help in preliminary studies, feasibility studies, and land use policy.